Pendampingan Jamaah Yasinan Untuk Revitalisasi Batik Celup Melalui Knowlegde Sharing - Mustofa, Idam; Miftahudin, Abd Hafidz; Sholikah, Mar’atus (LP3M STAI Darussalam Krempyang Nganjuk, 2020)
Community participation in an effective development framework can be developed by empowering the potential and assets of the local community. Community service in Jati Sawahan Lengkong Nganjuk succeeded in involving the role of micro businesses to carry out knowledge sharing techniques for making dyed batik for mothers of members of the yasinan group. The success of the service program is supported by mapping the potential and adequacy of social analysis so that it can map partner and target assets at the planning stage with sufficient data support. The success of the activity is supported by simultaneous coordination between stakeholders and the support of assets and potential of religious and community leaders and openness in accepting evaluations.